PENGGUNAAN PAIRED STORYTELLING UNTUK PENINGKATAN PEMBELAJARAN IPS TENTANG PROKLAMASI DAN PERJUANGAN MEMPERTAHANKAN KEMERDEKAAN INDONESISA SISWA KELAS V SD - Maemunah M, Siti (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The use of Paired Storytelling for Improving Learning of Social Studies about Proclamation and Struggle Keep Independence of Indonesia on The Student of Fifth Grade State Elementary School. The purpose of this research is to: improve learning of social studies about proklamation and struggle keep independence of Indonesia on the student of fifth grade state elementary school. The research consist of three cycles. The subjects of this researh are all students in the fifth grade of state elementary school 1 Dorowati which consist of 22 students. Sources of data in this study are students, peers, researchers, and documents. Data collection techniques that use in collecting the data were observation, documentation, interview, and testing. The validity of the data using triangulation sources and method. Data analysis in this study is a descriptive analysis techniques which include data reduction, data display, and conclusion. The results showed that the use of tecnic of Paired Storytelling, can improve student learning of social studies about proklamation and struggle keep independence of Indonesia on the student of fifth grade state elementary school. Keywords: Paired Storytelling, Social Studies Learning. Abstrak: Penggunaan Teknik Paired Storytelling untuk Peningkatan Pembelajaran IPS tentang Proklamasi dan Perjuangan Mempertahankan Kemerdekaan Indonesia Siswa Kelas V SD. Penelitian ini bertujuan: meningkatkan pembelajaran IPS tentang proklamasi dan perjuangan mempertahankan kemerdekaan Indonesia siswa kelas V SD. Penelitian dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah seluruh siswa kelas V SD Negeri 1 Dorowati yang berjumlah 22 siswa. Sumber data dalam penelitian ini adalah siswa, teman sejawat, peneliti dan dokumen. Teknik pengumpulan data menggunakan observasi, dokumentasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan metode. Bentuk analisis data dalam penelitian ini adalah teknik analisis deskriptif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan teknik Paired Storytelling, dapat meningkatkan pembelajaran IPS tentang proklamasi dan perjuangan mempertahankan kemerdekaan Indonesia siswa kelas V SD. Kata Kunci: Teknik Paired Storytelling, Pembelajaran IPS.